Sol-gel encapsulation of biomolecules and dells for medicinal applications - Wang, Xiaolin (2015)
The sol-gel process provides a robust and versatile technology for the immobilization of biologicals. A wide range of inorganic, composites and hybrid materials can be prepared to encapsulate molecular drugs, proteins, antibodies/antigens, enzymes, nucleic acids, prokaryotic and eukaryotic cells into bulk gels, particles and films. This review describes the applications of sol-gel encapsulation relevant to medicinal chemistry focusing on the recent development of biosensors as well as systems for production, screening and delivery of bioactive compounds and biomaterials.